New technologies – the impact on contemporary management accounting - Rybicka, Karolina (Research Papers of Wrocław University of Economics, 2018)
Contemporary enterprises must deal with changes in turbulent surrounding. New technologies are present in all societies. One effect of the explosion in the adoption of social media technologies has been the growth of so-called “Big Data”. Social media and Big Data are changing accounting and accountability in companies, but often such changes take place outside accounting subsystems. Use of digital technologies and methods is essential to gather, store and process large amount of data. With Big Data technologies, despite some challenges, modern enterprises are able to deal with such large volume of data, provide better forecasts and business decisions. There is presented in the paper the influence of the new technologies on management accounting
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 515, s. 26-36
Keywords: new technologies; big data; management accounting; nowe technologie; rachunkowość zarządcza